ACHIEVING THE GOALS OF UNIVERSAL BASIC EDUCATION THROUGH SCIENCE, TECHNOLOGY AND MATHEMATICS EDUCATION - Bello, Rabiu Muhammad; Kamar, Yahaya M. (Sokoto Educational Review, 2013)
One of the goals of Universal Basic Education (UBE) is to ensure permanent literacy such that the child becomes a productive member of the society, positively affecting all spheres of human existence. Achieving the goals of UBE programme in Nigeria is anchored on the development of Science, Technology and Mathematics Education (STME). The challenges encountered in the execution of UBE programme are similar to those of educational programmes before it; ranging from poor funding to insufficient personnel and inappropriate curricula. The rationale for the introduction of STME in Nigeria is in tandem with the goals of the United Nations, UNICEF and AU in the attainment of the rights of the child. To ensure the attainment of the rights of the child, governments have established institutions and agencies, while schools and science educators have also keyed in by forming clubs and societies that advance the course of STME. Here, a case is made for an appropriate and unambiguous redesign of the curriculum to capture basic STME components at the foundational level of Nigeria's education.